2009
DOI: 10.1029/2008jc005062
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of Laptev Sea and Arctic Ocean halocline waters in response to atmospheric forcing

Abstract: [1] Combined d 18 O/salinity data reveal a distinctive water mass generated during winter sea ice formation which is found predominantly in the coastal polynya region of the southern Laptev Sea. Export of the brine-enriched bottom water shows interannual variability in correlation with atmospheric conditions. Summer anticyclonic circulation is favoring an offshore transport of river water at the surface as well as a pronounced signal of brine-enriched waters at about 50 m water depth at the shelf break. Summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 32 publications
8
95
3
Order By: Relevance
“…10 at f r of 30% and f i of -16%). This is in agreement with a bathymetry-steered export of Laptev Sea bottom water at the north-eastern border of the Laptev Sea (Bauch et al, 2009) and is also in accordance with a shift in freshwater storage between the Laptev and the East Siberian seas (Dmitrenko et al, 2008). This layer may also be formed in the East Siberian Sea, but if so the f i / f r signature and salinity would be identical to that of the south-eastern Laptev Sea waters; therefore it is not discussed separately here.…”
Section: New Siberian Islands and East Siberian Sea F R / F Isupporting
confidence: 89%
See 1 more Smart Citation
“…10 at f r of 30% and f i of -16%). This is in agreement with a bathymetry-steered export of Laptev Sea bottom water at the north-eastern border of the Laptev Sea (Bauch et al, 2009) and is also in accordance with a shift in freshwater storage between the Laptev and the East Siberian seas (Dmitrenko et al, 2008). This layer may also be formed in the East Siberian Sea, but if so the f i / f r signature and salinity would be identical to that of the south-eastern Laptev Sea waters; therefore it is not discussed separately here.…”
Section: New Siberian Islands and East Siberian Sea F R / F Isupporting
confidence: 89%
“…Therefore bottom waters from the Kara and Laptev shelf areas with enhanced influence of local polynya activity had a salinity of about 30 (Bauch et al, 2005), compared to a salinity of about 32 in bottom waters of the Laptev Sea, which had a reduced imprint of local polynya activity (Bauch et al, 2010). The spatial distribution of river water on the Siberian shelves shows strong gradients and interannual variations within the surface layer (Bauch et al, 2009). …”
Section: F R / F I Ratios At High River Water Fractionsmentioning
confidence: 99%
“…Observations of dissolved Barium in 1998(Taylor et al, 2003 The covariation of MW and FIFB section transports and inventories (Sect. 3.2.5) may be due to formation processes on the Siberian shelves (Bauch et al, 2009(Bauch et al, , 2011a. Within the Transpolar Drift, Jones et al (2008a) observed IFB patches at depths below 50 m in the Eurasian Basin, vertically isolated from the much shallower summer surface mixed layer.…”
Section: Changes In the Arctic Ocean Basinsmentioning
confidence: 96%
“…Regional ice formation processes also have a strong influence on freshwater inventories by the release of subsurface brine maxima (e.g. Bauch et al, 2009Bauch et al, , 2011a from the shelves into the Arctic basins. These brine maxima have been observed to persist within the Transpolar Drift (e.g.…”
Section: Tracers and Freshwater In The Arctic Oceanmentioning
confidence: 99%
“…In summer 2007 "onshore" atmospheric conditions prevailed in the Laotev Sea (Bauch et al, 2010). Such an "onshore" scenario forced by the prevailing wind patterns causes Eurasian river runoff from the Laptev Sea to flow preferably eastwards into the East Siberian Sea instead of leaving the shelf northwards (Guay et al, 2001;Dmitrenko et al, 2005;Zhang et al, 2008;Bauch et al, 2009Bauch et al, , 2011b. In the East Siberian Sea these waters may mix with local shelf waters and Pacific water from the Bering Strait.…”
Section: Balancing the Fresh Water Fraction In The Upper Water Columnmentioning
confidence: 99%